Preparation of tungsten diboride by a combination of boro/carbothermal reduction process and spark plasma sintering. Issue 13 (October 2022) - Long, Ying; Liu, Bo; Lin, Shiming; Lin, Hua-Tay
Abstract: Submicron tungsten diboride (WB2 ) powder was successfully synthesized with the ratio of WO3 :B4 C:C = 2:1.1:5. The effects of carbon sources (carbon black or graphite) and heat treatment temperatures (1100, 1200, 1300 ℃) on the phase composition and microstructure of the as-synthesized WB2 powder samples were studied. The results showed that ultrafine WB2 powders with oxygen content of 1.65 wt% and 2.04 wt% were obtained by carbon black and graphite at 1300 ℃, respectively. The relatively density of the as-sintered WB2 samples achieve ~ 91 % and ~ 87 % without any kind of sintering additive after spark plasma sintering at 1500 °C under 30 MPa for 10 min. The formation mechanism of the WB2 powders synthesized by boro/carbothermal reduction was proposed and verified by thermodynamic calculation according to the phases present in the powder synthesized at different temperatures.